Canadian Railways and Unions in the Running Trade, 1865-1914 - Tuck, J. (Relations industrielles / Industrial Relations, 1981)
This paper examines the history in Canada of the international unions for train and engine crews, from their entry into Canada until World War One. During this period, patterns of unionization and labour-management relations in this important sector of the Canadian railway industry were established which have persisted in large measure to the present.